FPGA Prototyping of Micro-Blaze soft-processor based Multi-core System on Chip - Prasad Acharya, G; Asha Rani, M (International Journal of Engineering and Technology, 2018)
The increased demand for processor-level parallelism has many-folded the challenges for SoC designers to design, simulate and verify/validate todayâ€™s Multi-core System-On-Chip (SoC) due to the increased system complexity. There is also a need to reduce the design cycle time to produce a complex multi-core SOC system thereby the product can be brought into the market within an affordable time. The Computer-Aided Design (CAD) tools and Field Programmable Gate Arrays (FPGAs) provide a solution for rapidly prototyping and validating the system. This paper presents an implementation of multi-core SoC consisting of 6 Xilinx Micro-Blaze soft-core processors integrated to the Zynq Processing System (PS) using IP Integrator and these cores will be communicated through AXI bus. The functionality of the system is verified using Micro-Blaze system debugger. The hardware framework for the implemented system is implemented and verified on FPGA.Â Â